Real Time Assessment of Patients’ Body Oxygen Balance and Tissue Metabolic Score (TMS) - Avraham Mayevsky; Michael Tolmasov; Mira Mandelbaum (Medical Science: Trends and Innovations Vol. 4, 2025)
All major surgeries of patients performed under general anesthesia, require monitoring of vital functions performed by the cardiovascular and the respiratory systems. It is very important to monitor the vital signs such as ECG, heart rate, blood pressure, respiration and oxygen saturation of the blood. During the perioperative period of cardiovascular surgeries, an imbalance between oxygen supply and demand may lead to postoperative cognitive decline that may affect about 20% of the operated patients. In order to minimize the development of brain damage, few companies have developed monitoring devices that could provide real-time information regarding brain oxygenation, brain electrical activities or cerebral blood flow. Nevertheless, this approach is not the appropriate way to detect an early warning signal that may serve as an indicator of brain-negative oxygen balance. The alternative approach is to monitor the tissue oxygen balance of one of the less vital organs in the body that may serve as an early warning signal of deterioration of body oxygen balance. In this review, the use of a multiparametric monitoring device (CritiView) connected to the patient’s urethral wall via a 3-way Foley catheter that measures in real-time 4 parameters representing tissue oxygen balance. Mitochondrial NADH is measured by surface fluorometry/reflectometry. In addition, tissue microcirculatory blood flow, tissue reflectance and hemoglobin oxygenation are measured as well. The measured four (4) parameters could be integrated together with systemic hemodynamic parameters to provide in real time a new Tissue Metabolic Score (TMS). The device was tested both in vitro and in vivo in a small animal model and in preliminary clinical trials in patients undergoing vascular or open heart surgery. In patients, the monitoring started immediately after the insertion of a 3-way Foley catheter (urine collection) to the patient and was stopped when the patient was discharged from the operation room. The results show that monitoring the Urethral wall oxygen balance provides information in correlation to the surgical procedure performed. The CritiView results may serve as early warning signals to the deterioration of the body or the end point of resuscitations during and after cardiovascular surgeries.